Assessment of Shiranish and Pilaspi Limestone for Concrete Aggregates, Shaqlawa Area, Iraqi Kurdistan Region - Hakeem, Farhad A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Limestone of Shiranish and Pila Spi formations were evaluated as concrete aggregates through this study. For this purpose two outcrops had been selected; the first outcrop is Pila Spi Formation at Pirmam Anticline, and the second outcrop is Shiranish Formation at Safin Anticline. Both outcrops are located in the High Folded Zone, between Erbil and Shaqlawa cities. Chemical analysis for the studied samples shows that the limestone of Shiranish Formation has more calcite proportion, while the limestone of Pila Spi Formation is dolomitic. This was supported by the X-ray analysis and staining process by Alizarin Red S. To assess the studied limestone for concrete aggregate, the samples have been crushed and sieved into two grades, 4-30 mm (coarse aggregate) and finer than 4 mm (fine aggregate). The coarse portion is used instead of pebble and the fine portion is used instead of sand in concrete mixture. Eight briquettes with dimensions of 15 cm3 for each sample were formed. Two ratios of cement: fine aggregates: coarse aggregates were tested; 1: 1.5: 3 and 1: 2: 4 respectively. These raw materials were mixed with water in two ratios; 1:0.5 and 1: 0.75 for cement: water ratio respectively. The compressive strength tests show that the concrete prepared from Shiranish limestone aggregate give best results when compared with that prepared from Pila Spi limestone aggregate. These results proved that the Pila Spi limestone is suitable for using as aggregate in manufacturing concrete masonry only after twenty eight days of soaking in water. While Shiranish limestone is suitable for using as an aggregate in manufacturing concrete masonry after seven and twenty eight days soaking in water, as well as aggregate in manufacturing concrete foundation, column and roof after twenty eight days soaking in water. In addition to that, other concrete briquettes were formed from both formations, after soaking the limestone aggregates in water for 24 hours and showed bad results in the term of consistency.
Keywords: Crushed limestoneAggregateCompressivestrengthConcrete